THE NEW GOLD STANDARD IN LAPAROSCOPIC IMAGING: 3D VS 4K LAPAROSCOPIC NEPHRECTOMY- A SINGLE CENTERED RANDOMIZED CONTROLLED TRIAL - Kiani, Nauman Sadiq; Qazi, Sherjeel Saulat; Sheikh, Jahanzeb; Awais Ayub; Hamza Ashraf; Qadri, Syed Saeed Uddin; Mansoor Ejaz (Journal of Ayub Medical College Abbottabad, 2022)
Background: Thanks to progressive technology and modern innovations, laparoscopic procedures, being minimally invasive, have now supervened upon most open surgical procedures. Laparoscopic procedures have proven advantages over open procedures. The study was designed to compare the outcomes of laparoscopic nephrectomy between 3D and 4K camera resolutions. Methods: This randomized control trial carried out at Tabba Kidney institute, Karachi, Pakistan from July 2020 to April 2021, to our knowledge was the first of its kind comparative study in Pakistan and internationally. All patients diagnosed to have symptomatic non-functioning kidney on the basis of both renal scintigraphy and CT- KUB were divided through blocked randomization in to two different camera resolution groups, i.e., 3D vs 4K and outcomes in terms of operative time, haemoglobin fall, post procedure complications and in patient stay were recorded. Results: It was observed that the 3D group had a significantly shorter mean total operative time 172.1±36.9 vs 272.5±14.1 respectively (p<0.005). A significant difference was also observed in mean operative time for task 2 was 53.1±21.1 & 101±30.9 mins (p<0.005), and for task 3 was 67.18±18.3 & 112.5±37 mins (p=0.005) for 3D and 4K groups respectively. The mean haemoglobin drops in 3D and 4K groups was 0.51±1.6 & 0.73±1.1 respectively (p=0.7). Moreover, the mean hospital stay was 2.5±0.6 for 3D group & 2.7±0.9 for 4K group (p-value 0.8). Post-operative wound infection was observed in one patient in each group. No case had to be converted to surgery by an open approach. Conclusion: We concluded that despite being the latest technological advancement with a greater zooming capability, when used for performing laparoscopic nephrectomy, 4K imaging system couldn’t show any superiority over 3D imaging system, in different operative tasks and in terms of total operative time.